Acceptance Rate of Independent Exercise Mobile Based Learning Application Using Android - Arifah Bintarti; Djoko Rahardjo (Universitas Terbuka, 2021)
Universitas Terbuka (UT) has prepared many learning services, one of which is Independent Exercises that can be used by students in the learning process. The still low utilization of IE by students needs to be examined. This paper will discuss the extent of IE-based mobile learning using Android. This study uses a quantitative descriptive method, with a population of 180 respondents, and with a sample of 71 respondents form the cities of Serang, Bogor, Bandung, Yogyakarta, Manado,and Pangkal Pinang. Te results of the study show that the aspects of the ease of use, the usefulness, and the intention to use the Android Indepedent Exercises application generaly accepted by students, and it is supported by the access rate of them. Universitas Terbuka (UT) telah menyiapkan banyak layanan pembelajaran, salah satunya adalah Latihan Mandiri yang dapat digunakan oleh mahasiswa dalam proses pembelajaran. Masih rendahnya pemanfaatan IE oleh mahasiswa perlu dicermati. Makalah ini akan membahas sejauh mana pembelajaran mobile berbasis IE menggunakan Android. Penelitian ini menggunakan metode deskriptif kuantitatif, dengan jumlah populasi 180 responden, dan dengan sampel 71 responden dari Kota Serang, Bogor, Bandung, Yogyakarta, Manado, dan Pangkal Pinang. Hasil penelitian menunjukkan bahwa aspek kemudahan penggunaan, kemanfaatan, dan niat menggunakan aplikasi Latihan Mandiri Android secara umum diterima oleh siswa, dan didukung oleh tingkat akses mereka.